Objective and subjective career success: individual, structural, and behavioral determinants on European hybrid workers - Hildred, Kiall; Piteira, Margarida; Cervai, Sara; Pinto, Joana Carneiro (Frontiers in Psychology, 2023)
Introduction In the current worldwide labor context, where a disruption took place and employees experience. Methods Participated in this study 739 European hybrid workers who fulfilled an online assessment protocol. Results Results indicate that higher ages, higher educational levels, being married, having children, working. Discussion This study makes a unique contribution to the extant research on hybrid workers’ careers, specifically.